The Science of Safety - An Emerging Concept in Medication Use and Research - Shraddha Shinde, MBA student; Stephanie Y Crawford, PhD (University of Minnesota Libraries Publishing, 2016)
Most published reports of patient safety in clinical practice focus largely on the culture of safety in complex health systems, separate from pre-approval and postmarketing research-related safety considerations for drugs, biologics, and other medical products. The science of safety requires a linked integrated perspective, i.e., an iterative process examining and relating safety concerns from drug or biologic discovery and development in preclinical stages, clinical trials and post-market use, research, surveillance, and potential regulatory changes. This commentary addresses the science of safety across the lifecycle of drug and biological products, regulatory considerations, barriers, and research needs. This paper provides a brief overview on how the functioning of healthcare systems affects the safety environment and describes how stakeholder involvement, research participation, and targeted education and training can help facilitate better safety measures and practices, provide improved quality of care to patients, and contribute to the science of safety. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties".   Type: Commentary